Vulnerabilidade de acessos de sementes de Erythrina velutina Willd. (Fabaceae) a estresses abióticos - Sena, Eliza Maiara Nogueira de (2017)
The stress situation in Caatinga is aggravated by climate changes, from which are predicted higher temperatures; water scarcity and higher soil salinization. Studies evaluating differences in seeds tolerance to abiotic stress among samples or genotypes of the same species can constitute physiologic tools and significant and complementary information for the selection of the most adapted group to environmental pressures. This work aimed to compare the seed vulnerability of different samples of Erythrina velutina (Fabaceae) to abiotic stress; evaluate que physiologic quality of seeds and determine the tolerance limits to saline, hydric and thermic stress. The assays were conducted at EMBRAPA semiarido Seeds laboratory and at the Germination laboratory of State University of Feira de Santana. In addition, the assays were entirely randomly mounted, four repetitions of 10 seeds for the vigor test and 50 seeds for the stress test. In the initial vigor, the seeds of all samples showed 100% of radicle emission at the first count. The seeds samples were affected by the addition of sodium chloride in the solution, exhibiting critical limit at 36dSm-1 for some samples. The radicular protrusion was affected with the decrease of the osmotic potential of the solution, which was caused by PEG 6000, limiting the germination in -0,9 MPa. The seed germination of E. velutina occurs at broad limits of temperature, from 5 to 40°C. Generally, the stress imposed by sodium chloride and PEG did not compromise the viability of the seed germinal power as the seeds of the samples showed high rate of germination when the ideal conditions were reestablished, excepting Caiçara 2011. The great temperature of E. velutina germination occurs between 25 to 30°C.